(untitled) (Baghdad Science Journal, 2025)
In this study we surveyed the dominant normal stool flora of randomly selected healthy, young (18-23 years old), unmarried (doctrinal) Iraqi college students (males and females) for the carriage of extraintestinal pathogenic E. coli (ExPEC). ExPEC virulence was detected phenotypically by mannose resistant hemagglutination of human red blood cells (MRHA) and mannose sensitive (MS) agglutination of Bakers’ yeast (Saccharomyces cerevisceae). From 88 college students, 264 E. coli isolates were obtained (3 isolates per person): 123 from 41 females and 141 from 47 males. Of these isolates, 56% (149/264) caused MS agglutination of yeast cells and 4.16% (11/264) showed MRHA. Eighty two percent (9/11) of the isolates with MRHA also caused MS agglutination of yeast cells. Statistically the difference is not significant (P < 0.05) among males and females regarding the MS agglutination of yeast cells: 59% (72/123) of females’ isolates vs. 55% (77/141) of males’ isolates. Conversely, the difference is clear regarding the carriage of isolates with MRHA. All the isolates with MRHA were distributed among females’ dominant stool flora (11/123: 8.94%) whereas none of the males’ dominant stool flora showed MRHA (0/141: 0%). Five females out of 41 (12.19%) had isolates with MRHA. All the three isolates in 2 of these 5 females showed MRHA, 2 isolates in another 2 showed MRHA, and only one isolate in 1 female caused MRHA. Therefore we can say that the difference among males and females in fecal carriage of E. coli ,with characteristics of ExPEC, can be a predisposing factor of females to ExPEC infections more than males.